Peran Ta’awun dalam Mengentas Kemiskinan di Kota Makassar - Zulkarnain; Abdul Wahab; Syaharuddin Syaharuddin (Al-Buhuts, 2020)
This study aims to determine the role of ta'awun in the community of Makassar City in alleviating poverty and to find the inhibiting factors that exist in the implementation of ta'awun and their solutions. This study uses a phenomenological approach as the main approach and is assisted by a pedagogical approach. The results of this study indicate that ta'awun has the opportunity and potential to alleviate poverty in Makassar City. The inhibiting factors of the application of ta'awun are the poor social ethics of the community, the existence of social stratification, and the lack of understanding of religion. The solution to these obstacles is to maximize the role of the government, community leaders, and religious leaders in terms of the policy, education, and socialization of the importance of ta'awun behavior.